Extreme Sawtooth-Sign in Motor Neuron Disease (MND) suggests Laryngeal Resistance to Forced Expiratory Airflow. (March 2023) - Britton, Deanna; Kain, Alexander; Chen, Yu-Wen; Wiedrick, Jack; Benditt, Joshua O.; Merati, Albert L.; Graville, Donna
Objective: The impact of laryngeal dysfunction on airflow has not been well characterized in motor neuron disease (MND). This study aimed to detect and characterize extreme airflow oscillations informally observed during volitional cough and forced vital capacity (FVC) tasks in individuals with MND who demonstrated neurolaryngeal impairments including reduced speed and extent of vocal fold abduction compared to healthy controls during volitional cough expulsion. The extreme airflow oscillations in the MND group, when viewed as a flow-volume loop, appeared similar to the "sawtooth-sign." If the airflow oscillations are periodic in a range similar to phonation, they may reflect reduced laryngeal patency. Methods: Volitional cough and FVC airflow data (3 trials each) from 12 participants with MND with bulbar/laryngeal involvement (3 F; ages 45-76) and 12 healthy controls (6 F; ages 41-68) were analyzed for periodicity. Percent and absolute durations of periodicity of the flow oscillations were calculated by an algorithm applied to the airflow signals. In addition, the frequency, magnitude, and kurtosis of the periodic airflow oscillations were described and compared between groups. Results: In both volitional cough and FVC trials, the percent of airflow periodicity during forced expiration was significantly higher ( z = 3.54) in individuals with MND, adjusted for age and sex. Periodic airflow accounted for on average 28% of the total time in participants with MND and was within a frequency range similar to phonation. Magnitude of the airflow oscillations was also larger for participants with MND ( z = 3.46), and kurtosis of airflow was smaller ( z = −4.70) during forced expiration, indicating persistent airflow oscillations throughout exhalation. Conclusions: The significantly larger-magnitude, lower-kurtosis, and more prominent presence of sawtooth-like airflow periodicity within a frequency range similar to phonation observed in individuals with MND with neurolaryngeal impairments suggests glottic airflow resistance during forced expiration.